Study Of Market Timing, Selectivity And Performance Of Equity Unit Trust Funds In Malaysia - Jaafar, Norlida (2010)

(untitled)
The main objective of this study is to re-look at the performance of the unit trust industry given that this industry has grown tremendously over the past years. Data of public and private funds from January 1991 to December 2004 was used, which were further sub divided into pre-crisis period, crisis period and post crisis period. The main focus of this study is on the contribution of market timing and selectivity strategies on the performance of unit trust funds. This study is a wider study on the subject of unit trust funds ad the evaluation focused at three aspects that is the effect of these practices over different time horizon, different benchmarks and the assessment of the funds under the same management.